Writing for publication: Structure, form, content, and journal selection. Issue 6 (June 2021) - Phillips, Veronica; Barker, Eleanor
This article provides an overview of writing for publication in peer-reviewed journals. While the main focus is on writing a research article, it also provides guidance on factors influencing journal selection, including journal scope, intended audience for the findings, open access requirements, and journal citation metrics. Finally, it covers the standard content of a scientific journal article, providing general advice and guidance regarding the information researchers would typically include in their published papers.